Breastfeeding significant correlated with decreasing of breast cancer risk - Muharram, Girry Gustianugraha; Darmi, Noer Faisal; Razi, Fachrul (Surgical Residency Program Syiah Kuala University, 2023)
Background: Extensive literature has established a strong correlation between breastfeeding and a decreased susceptibility to breast cancer. The objective of this study was to examine the breastfeeding status of moms diagnosed with breast cancer. Methods: This study employs a descriptive-analytical approach with a cross-sectional design. The study comprised adult female patients (aged 20-60) who were diagnosed with Breast Cancer, irrespective of the specific kind of cancer confirmed by anatomical pathological investigation. Only non-smokers were considered for analysis. The study excluded patients who had a history of malignancy and those with a family history of cancer. A bivariate analysis was performed to evaluate the study hypothesis. The analysis was conducted utilizing the Chi-Square and unpaired T-test statistical methods using SPSS software. A p-value less than 0.05 is deemed statistically significant. Result: This research encompassed a total of 45 individuals diagnosed with breast cancer. The majority of individuals diagnosed with breast cancer (55.6% of the total) did not engage in exclusive breastfeeding. Similarly, individuals without a breast cancer diagnosis also tended to refrain from exclusive nursing (24.4%). The association between the two variables is statistically significant, as indicated by a p-value of 0.000. The average length of nursing in individuals diagnosed with breast cancer was 2.04 ± 1.81, but in those without breast cancer, it was 10.10 ± 9.01. The statistical tests indicate a substantial association between the two variables, as evidenced by a p-value of 0.000. Conclusion: A notable correlation exists between breastfeeding and a diminished likelihood of developing breast cancer.